Atypical form of early neonatal infection with Salmonella enterica: case report with literature review - Andrianirina, Zafitsara Z.; Tsifiregna, Rosa L.; Randriamahavonjy, Romuald; Bizet, J. (International Journal of Research in Medical Sciences, 2018)
Salmonella are rarely responsible for neonatal or perinatal infection. An annual incidence of 75/100000 births are reported in the USA. The authors present a case of a newborn with neonatal salmonellosis in the context of maternal infection in the days preceding the birth, documented retrospectively. This is a case of a 38-week male infant born via spontaneous vaginal delivery. There was a premature rupture of the membranes (13 hours). The mother gave a history of fever and diarrhea of ten days prior to delivery. She had fever of 38.3°C during labor. Prophylactic antibiotic treatment with amoxicillin was established. Thirty-two hours after birth, the baby developed fever, lethargy, and was not accepting feeds. On admission, physical examination showed fever, tachycardia, correct blood pressure and isolated jaundice. The blood count found a leukopenia, a thrombocytopenia, a CRP at 35mg/l. Parenteral antibiotic therapy with cefotaxime and amikacin was started. Apyrexia is obtained after 48 hours of intravenous treatment. Stool culture of the newborn grew after 48 hours and for the mother after 3 days. The germ identified was Salmonella enterica Serovar 4,5,12:i:-. Blood cultures were performed on the mothers and the baby, but the cultures were negative. The baby responded and was discharged on the 15th day of delivery. The mother’s condition was complicated by a Guillan Barré syndrome that required a transfer to neurology. Neonatal salmonellosis may have non-specific clinical symptoms. Management is based on early antibiotic therapy with a third-generation cephalosporin as first-line therapy. The measure in preventing the spread of infection in the neonatology is essential to avoid secondary cases.